Asset Prices, Monetary Policy, and the Business Cycle - Schinasi, Garry (Washington, D.C. : International Monetary Fund, 1994)
The business cycle in several industrial countries during the period 1989-1993 was different from previous post World War II business cycles in important ways. This paper describes the unique character of the recent cycle, examines important underlying structural and macroeconomic factors, and discusses why these unique features emerged. Although many of the structural changes were partly responsible for the overshooting of asset prices and private debt levels, the extreme overshooting could not have occurred without overexpansionary monetary and fiscal policies. The paper examines why inflationary pressures were allowed to accumulate and then discusses a number of lessons for conducting economic policy in the 1990s. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the authors) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet